The professor and the parson : a story of desire, deceit, and defrocking - Sisman, Adam (Counterpoint Press, 2020)
"One day in November 1958, the celebrated historian Hugh Trevor-Roper received a curious letter. It was an appeal for help, written on behalf of a student at Magdalen College, with the unlikely claim that he was being persecuted by the Bishop of Oxford. Curiosity piqued, Trevor-Roper agreed to a meeting. It was to be his first encounter with Robert Parkin Peters: plagiarist, bigamist, fraudulent priest, and imposter extraordinaire. The Professor and the Parson traces the strange career of one of Britain's most eccentric criminals. Motivated not by money but by a desire for prestige, Peters lied, stole, and cheated his way to academic positions and religious posts from Cambridge to New York, Singapore, and South Africa. Frequently deported, and even more frequently discovered, his trail of destruction included seven marriages (three of which were bigamous), an investigation by the FBI, and a disastrous appearance on Mastermind. Based on Trevor-Roper's own detailed "file on Peters," The Professor and the Parson is a witty and charming account of eccentricity, extraordinary narcissism, and a life as wild and unlikely as any in fiction"--